2018
DOI: 10.17811/ebl.7.1.2018.36-46
|View full text |Cite
|
Sign up to set email alerts
|

Age of the entrepreneurial decision: Differences among developed, developing, and non- developed countries

Abstract: Although entrepreneurship is widely considered an engine of growth, it is not clear whether policies, de facto, promote it, and knowing which individuals are willing to become entrepreneurs could help in the design of those policies. In this paper, we study how individuals become entrepreneurs at different ages, according to the degree of development of the country of residence. We make use of the GEM 2014 Adult Population Survey data, against a background where social norms are controlled, to find that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(24 reference statements)
7
9
0
3
Order By: Relevance
“…The analysis reflects 0,29% annual decrease in TEA after age 55, which is in line with the results of other research works which show that there is less entrepreneurial activity at a higher age (Coduras et al, 2018). That is, people perceive that they have less available time as they grow older, and there is an opportunity cost of time (Lévesque & Minniti, 2006).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The analysis reflects 0,29% annual decrease in TEA after age 55, which is in line with the results of other research works which show that there is less entrepreneurial activity at a higher age (Coduras et al, 2018). That is, people perceive that they have less available time as they grow older, and there is an opportunity cost of time (Lévesque & Minniti, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…The fact that the variables "know an entrepreneur" and "perceive the skills" are variables which positively affect the probability of becoming an entrepreneur in the case of Chile, is in line with other work which identifies factors which influence entrepreneurship in other regions (Coduras, 2018;Červeny, 2016;Holienka, 2016). It can be seen that the perception that one possesses the necessary skills to become an entrepreneur provides the highest marginal probability (0.11) to become an entrepreneur.…”
Section: Discussionsupporting
confidence: 81%
“…Entrepreneurial ties seem to have an impact on the process of innovation for nascent entrepreneurs and business owners, in line with the entrepreneurial network literature (Klyver, 2012). Conversely, age, gender, and household composition do not appear to drive innovation, although they are traditional predictors of entrepreneurship (e.g., Minniti, 2010;Coduras et al, 2018). Similarly, the fear of failure is also non-significant, despite prior research finding it as a means to ambition (Saiz-Alvarez et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…We include in our analysis a range of independent variables, including sociodemographic factors: age, measured in years; age squared (age 2 /100); gender; and education (basic, secondary, and University education, in terms of the highest level achieved). Prior research has shown how these variables can have an impact on entrepreneurial activity, so they may also be correlated with innovation among entrepreneurs (Minniti, 2010;Coduras et al, 2018). We also control for the number of children and the family size, labor experience (measured in years), the labor force status (employee, self-employed, student, and unemployed and retiree), and income levels (Castaño et al, 2015).…”
Section: Datamentioning
confidence: 99%
“…La edad es un aspecto relevante en el emprendimiento, algunos estudios han identificado que la juventud puede ser un factor determinante en la predisposición a emprender, de cualquier manera se trata de un factor a estudiar con el objetivo de priorizar las políticas a un segmento u otro de población, ya que los objetivos pueden variar en función de determinados contextos como el caso de querer afrontar el desempleo juvenil o promover el emprendimiento en colectivos jubilados (Coduras, Velilla, & Ortega, 2018). En el estudio desarrollado por la Asociación Europea para la innovación en materia de productividad y sostenibilidad a través de un grupo focal, igualmente se concluyó que los emprendedores agrarios pueden tener cualquier edad, aunque suelen ser jóvenes y se limitan a explotaciones pequeñas.…”
Section: (H2) Los Emprendedores Agrarios Son Más Jóvenes Que El Resto De La Población Y Emprendedores En Otros Sectoresunclassified